Task and Forced Instructional Strategy: Instructional Strategy Based on the Character and Culture of the Indonesian Nation - Leonard, Leonard (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
The application of instructional strategy must consider the characteristics and students' culture to get an optimal learning result. The Indonesian character is to be based on this strategy and not finish the task well if there is no compulsion or punishment. This character is a background of purpose tasks and forced instructional strategy. This strategy emphasised a routine task and a plan for the students, noticing the deadline for finishing the task and the punishment if the task is not finished well. This strategy can be an alternative strategy to increase learning quality, especially to develop the student's awareness about how studying is important for them.